2020
DOI: 10.1016/j.jtcme.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The gastroprotective effect of the foxtail millet and adlay processing product against stress-induced gastric mucosal lesions in rats

Abstract: Foxtail millet ( Setaria italica (L.) P. Beauv.) and adlay ( Coix lachryma-jobi L. var. ma-yuen Stapf.) seeds have substantial benefits possesses remarkable edible and nutritive values, and ease of processing and food manufacturing. They have nutraceutical properties in the form of antioxidants which prevent deterioration of human health and have long been used in traditional Chinese medicine as a remedy for many diseases. The present study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
(41 reference statements)
0
9
0
1
Order By: Relevance
“…Foxtail millet has long been considered healthy food that promotes gastrointestinal health in China. Lin showed that millet has a great beneficial effect on gastric mucosal barrier protection ( 10 ). Several studies reported that millet exhibit significant protective effects on the viability of Lactobacillus ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foxtail millet has long been considered healthy food that promotes gastrointestinal health in China. Lin showed that millet has a great beneficial effect on gastric mucosal barrier protection ( 10 ). Several studies reported that millet exhibit significant protective effects on the viability of Lactobacillus ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Millet porridge helps coordinate the intestines and stomach, tonify deficiency, and can stimulate the appetite. It also prevents indigestion and assists in treating gastric ulcers and digestive ulcers ( 10 ). Nutritional research on foxtail millet has revealed many health benefits, including blood-sugar-lowering effects ( 11 ), and anti-oxidative ( 12 ), antifungal ( 13 ), antihypertensive ( 14 ), and anti-inflammatory behavior ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reactive oxygen species (ROS) increase in ischemic tissue and are mediators of stress-induced gastrointestinal injuries. ROS trigger lipid peroxidation with subsequent loss of membrane integrity and cell death ( Lin et al, 2020 ). (-)-Carveol showed a gastroprotective effect in all doses evaluated, which suggests that gastric cytoprotection may be involved in this effect.…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to the antioxidants present in the grains that promoted ulcer protection by decreasing ulcer index, TBARS values, and increasing non-protein sulfhydryl (NPSH) concentrations. [17] Polyphenols (taxifolin and catechin)…”
Section: Foxtail Millet Gastro-protective Propertymentioning
confidence: 99%